Daya Dukung Kualitas Air Terhadap Usaha Budidaya Ikan Patin Dalam Kolam Di Kabupaten Banjar Kalimantan Selatan - Irma Febrianty (Universitas Lambung Mangkurat, 2020)
The business of catfish farming in ponds must be supported by good environmental conditions so that the growth of catfish can be optimal, but the problem in Banjar Regency, in general, is acidic water, this can affect catfish production. The purpose of this study is to analyze the carrying capacity of the environment for catfish culture in ponds. The analysis used is water quality analysis. The results of the water quality study of Station 1 obtained an excellent value because the value of important parameters such as Ammonia and DO obtained the best value. The excellent value if the results from the field data for parameters that are very influential on catfish cultures such as DO, pH, ammonia, turbidity, and temperature have values that are in the ideal range based on PP No. 82 of 2001.